Growth and characterization of InSb on (1 0 0) Si for mid-infrared application - Jia, Bo Wen (2019)
Monolithic integration of InSb on (1 0 0) Si is a practical approach to realizing on-chip mid-infrared photonic devices. An InSb layer was grown on a (1 0 0) Si substrate using an AlSb/GaSb buffer containing InSb quantum dots (QDs). The growth process for the buffer involved the growth of GaSb on Si using an interfacial misfit array, followed by InSb QDs on AlSb to decrease the density of microtwins. InSb layers were separately grown on AlSb and GaSb surfaces to compare the effect of different interfacial misfit arrays. The samples were characterized using transmission electron microscopy and X-ray diffraction to determine the structural properties of the buffer and InSb layers. The InSb on the AlSb sample exhibited higher crystal quality than the InSb on GaSb sample due to a more favorable arrangement of interfacial misfit dislocations. Hall measurements of unintentionally doped InSb layers demonstrated a higher carrier mobility in the InSb on the AlSb sample than in InSb on GaSb. Growing InSb on AlSb also improved the photoresponsivity of InSb as a photoconductor on Si.